PACHYCHOROID: An Inherited condition?. Issue 1 (January 2015) - Lehmann, Mathieu; Bousquet, Elodie; Beydoun, Talal; Behar-Cohen, Francine
Abstract : Purpose: Thick choroid (pachychoroid) is associated with central serous chorioretinopathy (CSC), but whether pachychoroid is inherited is unknown. Methods: In a prospective observational study, first- or second-degree relatives (16 individuals) of 5 patients with CSC had refraction and visual acuity measurement, fundus examination, nonmydriatic photography, and autofluorescence photography. Eyes were graded using the following criteria: 0: normal fundus and autofluorescence photography, 1: focal retinal pigment epithelium hyperfluorescence and/or hypofluorescence and/or retinal pigment epithelial detachment, 2: CSC or diffuse retinal epitheliopathy. Choroid thickness was measured by enhanced depth imaging mode on optical coherence tomography. Results: Considering 395 μ m as the threshold limit for normal subfoveal choroidal thickness, 50% of the eyes from relatives had a thick choroid. Nine eyes of Grade 0 (28%) with an isolated pachychoroid would thus have been considered normal, if choroidal thickness was not included as a screening sign predisposing for CSC. Conclusion: Our observation suggests that pachychoroid could be an inherited condition with potentially a dominant transmission mode. Its inclusion in the phenotype of CSC for genetic studies should be considered. Abstract : Isolated pachychoroid is observed in first and second-degree relatives of patients with central serous chorioretinopathy, suggesting a dominant transmission of this condition. Pachychoroid could be an inherited predisposing factor for central serous chorioretinopathy, and it should be considered when phenotyping individuals in central serous chorioretinopathy genetic studies.